2020
DOI: 10.1111/jth.14765
|View full text |Cite
|
Sign up to set email alerts
|

Tetra positive thrombotic antiphospholipid syndrome: Major contribution of anti‐phosphatidyl‐serine/prothrombin antibodies to lupus anticoagulant activity

Abstract: Background:The concurrent presence of lupus anticoagulant, anticardiolipin, and anti β2-glycoprotein I antibodies (triple positive profile) identifies patients at high risk of thromboembolic events. These patients are also positive for anti-phosphatidylserine/prothrombin antibodies (tetra-positive profile).Objective: Understand which antibody among anti-β2-glycoprotein I and anti-phosphatidyl-serine/prothrombin is responsible for lupus anticoagulant activity.Patients/Methods: Affinity purified anti-β2-glycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 31 publications
5
63
3
Order By: Relevance
“…This indicates that aPS/PT are not responsible for the prolongation of aPTT nor are predictors of adverse clinical outcomes. Furthermore, in contrast to what we would have expected in APS ( 32 ), we found no associations between the presence of aPS/PT, aCL, and anti-β 2 GPI antibodies. This data is in line with the unusual epitope specificity of anti-β 2 GPI antibodies documented in Figure 2 , supporting the hypothesis that aPL found in COVID-19 patients are different from aPL found in APS patients.…”
Section: Discussioncontrasting
confidence: 99%
“…This indicates that aPS/PT are not responsible for the prolongation of aPTT nor are predictors of adverse clinical outcomes. Furthermore, in contrast to what we would have expected in APS ( 32 ), we found no associations between the presence of aPS/PT, aCL, and anti-β 2 GPI antibodies. This data is in line with the unusual epitope specificity of anti-β 2 GPI antibodies documented in Figure 2 , supporting the hypothesis that aPL found in COVID-19 patients are different from aPL found in APS patients.…”
Section: Discussioncontrasting
confidence: 99%
“…It should be underlined that different antiphospholipid (aPL) laboratory profiles are not equivalent in predicting future thromboembolic events and that their clinical relevance is quite different. Triple positivity (in most cases tetra positivity 18 ) is always confirmed after 12 weeks, whereas single test positivity is confirmed after 12 weeks in <50% of cases 19 . All 14 participating centers confirmed the presence of triple‐positive aPL profiles during the 2‐year follow‐up after TRAPS closure.…”
Section: Resultsmentioning
confidence: 82%
“…17 It should be underlined that different antiphospholipid (aPL) laboratory profiles are not equivalent in predicting future thromboembolic events and that their clinical relevance is quite different. Triple positivity (in most cases tetra positivity 18 ) is always confirmed after hypertension. 20,21 Moreover, all 14 catastrophic APS seen in the Padua hospital were triple-positive patients.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…[1][2][3] Testing for lupus anticoagulant (LA) is mandatory to detect triple-pos- with APS and triple positivity are also positive in aPS/PT (tetra-positive aPL) 7 and that aPS/PT more than aβ2GPI is responsible for LA activity in these patients. 8 Finally, if aCL and aβ2GPI antibodies are of immunoglobulin G (IgG) isotype I would measure IgG aβ2GPI/domain 1 antibodies that are associated to thromboembolic events. 9 A tentative decision-making scheme to choose the appropriate anticoagulant treatment in young patients with venous thromboembolism is presented in Figure 1.…”
Section: Additional Laboratory Tests To Improve On the Diagnosis Of Amentioning
confidence: 99%
“…At the same time, I would check anti–phosphatidyl‐serine/prothrombin (aPS/PT) antibodies that can be used as a surrogate test for LA. We have recently shown that most patients with APS and triple positivity are also positive in aPS/PT (tetra‐positive aPL) 7 and that aPS/PT more than aβ2GPI is responsible for LA activity in these patients 8 . Finally, if aCL and aβ2GPI antibodies are of immunoglobulin G (IgG) isotype I would measure IgG aβ2GPI/domain 1 antibodies that are associated to thromboembolic events 9 …”
Section: Figurementioning
confidence: 99%